Potential Transfer of Peanut and/or Soy Proteins from Poultry Feed to the Meat and/or Eggs Produced - Toomer, Ondulla T. (ACS Omega, 2020)
[Image: see text] Previous studies have demonstrated that allergenic feed proteins from peanuts in the diets of layer hens are not detected in the eggs produced. Hence, in this study, we aimed to determine if soy and/or peanut proteins in poultry feed rations of broiler chickens or layer hens would be transferred or detectable in the meat or eggs produced. To meet this objective, 99 layer hens and 300 broiler chickens were equally divided into treatment groups and fed one of three experimental diets: control soybean meal and corn diet, whole unblanched high-oleic peanut and corn diet (HO PN), or a control diet spiked supplemented with oleic acid (OA) oil. At termination, broiler chickens were processed, and chicken breast samples of the left pectoralis muscle were collected, and eggs were collected from layers. Total protein extracts from pooled egg samples and chicken breast samples were subjected to enzyme-linked immunosorbent assay (ELISA) methods and immunoblotting analysis with rabbit antipeanut agglutinin antibodies and rabbit antisoy antibodies for the detection of peanut and soy proteins. Peanut and soy proteins were undetected in all pooled egg samples and individual chicken breast meat samples using immunoblotting techniques with rabbit antipeanut agglutinin and rabbit antisoy antibodies. Moreover, quantitative ELISA allergen detection methods determined all pooled egg samples and individual meat samples as “not containing” peanut or soy allergens. Therefore, this study helps to evaluate the risk associated with the potential transfer of allergenic proteins from animal feed to the products produced for human consumption.